Platysetosus occultus gen. nov., sp. nov., a new genus and species of mite from Tasmania (Acari: Uropodina) - Dylewska, M.; Błoszyk, J.; Halliday, R. B. (Zootaxa, 2006)
A new endemic Australian genus Platysetosus gen. nov. (Acari: Uropodina: Uropodoidea) from Tasmania and its type species Platysetosus occultus sp. nov. are described and figured. Platysetosus is very distinctive, and its relationship to other genera of Uropodina is not clear.